ETHNOBOTANICAL STUDY OF JAVA ACID PLANT (Tamarindus indica) IN PAGATAN BESAR VILLAGE, TANAH LAUT REGENCY - Riya Irianti Irianti; Amalia Rezeki Rezeki; Shafa' Muthi'ah Muthi'ah (Universitas Negeri Medan, 2023)
Ethnobotany is a branch of biology that studies the use of plants by an ethnic group in a certain area for life needs such as food, medicine, dyes, building materials, ritual ceremonies, myths, and so on. This study aims to describe the Ethnobotany of Java Acid plant (Tamarindus indica) in Pagatan Besar Village, Tanah Laut Regency. This research methods using qualitative descritives. The results of the study show an Ethnobotanical study of the Java Acid plant (Tamarindus indica) with a tree habit where the leaves are believed to be able to treat smallpox wounds and the fruit is used as a medicine for coughs and bruises (pharmacology). The Java Acid plant (Tamarindus indica) is used as a pisit at civil ceremony events (weddings) and as a condition for giving to midwives who assist in childbirth (socioanthropology). Java Acid plant (Tamarindus indica) is useful as greenery and shade (ecology). This plant is called Asam Kamal by the local community because it comes from the Banjar language, from the word Java Acid because it tastes sour and kamal which means lump or lump (linguistic) which is used as a mixture when cooking, a mixture of pickles, sour candies, and charcoal (economy).